Experimentally validated structural finite element method analysis of a tibial intramedullary nail: Optimal choice of the contact settings. (February 2019) - Croccolo, D; De Agostinis, M; Fini, S; Funaioli, S; Olmi, G; Robusto, F
This article focuses on the static structural analysis of a tibial intramedullary nail, carried out by the finite element method. The investigated subject is concerned with the issue of frictional contacts that, generating a non-linear problem, play an important role in numerical analyses. Experimental tests were also developed on tibial intramedullary nail specimens. The experimental results, in terms of force–displacement, were used to calibrate and validate the finite element analysis, by tuning the contact parameters available in the software.